Study on the potential of repair fire-damaged reinforced concrete beams using ultra high performance concrete with curing at ambient temperature - Muhd Afiq Hizami, Abdullah (Universiti Malaysia Perlis (UniMAP), 2016)
Master of Science in Civil Engineering